2021
DOI: 10.1155/2021/9917810
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Activity, Polyphenolic Content, and FT-NIR Analysis of Different Aspilia africana Medicinal Plant Tissues

Abstract: Aspilia africana has been used for generations to treat many diseases in Africa. Its biological activities, including antioxidant and anti-inflammatory potential, are attributed to a number of secondary metabolites, including alkaloids and polyphenolics. The antioxidant activities of A. africana callus (CA), juvenile in vitro leaf (IL) and root (IR), ex vitro root (SR) and leaf (SL), and wild leaf (WL) dried samples were assessed based on their diphenylpicrylhydrazyl (DPPH) free radical scavenging abilities. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 46 publications
1
18
0
Order By: Relevance
“…The biological activities of medicinal plants, such as antioxidant, antimicrobial, and anti-inflammatory activities, largely depend on these phytochemicals. We found that the in vitro regenerated tissues had high antioxidant activity (Okello et al, 2021a). These in vitro regenerated plant tissues could be a valuable natural source of antioxidants and could be further exploited for the development of useful pharmaceutical products (Okello et al, 2021a).…”
Section: Discussionmentioning
confidence: 94%
See 4 more Smart Citations
“…The biological activities of medicinal plants, such as antioxidant, antimicrobial, and anti-inflammatory activities, largely depend on these phytochemicals. We found that the in vitro regenerated tissues had high antioxidant activity (Okello et al, 2021a). These in vitro regenerated plant tissues could be a valuable natural source of antioxidants and could be further exploited for the development of useful pharmaceutical products (Okello et al, 2021a).…”
Section: Discussionmentioning
confidence: 94%
“…We found that the in vitro regenerated tissues had high antioxidant activity (Okello et al, 2021a). These in vitro regenerated plant tissues could be a valuable natural source of antioxidants and could be further exploited for the development of useful pharmaceutical products (Okello et al, 2021a).…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations